Hyers-Ulam Stability of Functional Equation Deriving from Quadratic Mapping in Non-Archimedean n, β-Normed Spaces. (4th May 2021) - Alessa, Nazek; Tamilvanan, K.; Loganathan, K.; Selvi, K. Kalai
Abstract : In this work, we have to introduce a generalized quadratic functional equation and derive its solution. The main objective of this work is to investigate the Hyers-Ulam stability of quadratic functional equation in non-Archimedean n, β -normed spaces.